Religion and politics: cultural perspectives - Giesen, Bernhard; Šuber, Daniel (Brill, 2005)
The volume collects eminent works on the relationship between politics and religion by leading figures in Cultural Studies. The contributors share in the basic belief that the roots of contemporary conflicts have to be uncovered from the historical descent of religion
Includes bibliographical references and index. - Description based on print version record
Keywords: Konstanz <1999-2003>; Electronic books; Electronic books -- Conference proceedings; Konferenzschrift; Aufsatzsammlung; Politik; Religion